KAJIAN FILSAFAT HUKUM TERHADAP PELAKSANAAN PIDANA MATI MENURUT HAK AZASI MANUSIA (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
The provisions of article 10 of the Criminal Code (CRIMINAL CODE) state that in addition to 4 (four) main criminal types, namely: death penalty, imprisonment, imprisonment and fines, there are 3 (three) additional criminal types, namely the revocation of certain rights, confiscation of certain goods, and the announcement of the judge's decision. The death penalty is the most severe type of criminal in the composition of sanctions and is one of the main forms of criminal. The existence of the death penalty is basically a type of criminal that robs a legal interest (rechtsbelang), which is in the form of human life. The existence of the death penalty among jurists there is a difference of opinion. The formulation of the issue raised is how the execution procedure for death row inmates is viewed from the human rights side. The type of research used is normative juridical with a statutory approach. The results found that the death penalty has existed since antiquity through the regulation of positive laws, customary laws, and religion. The death penalty is a guarantee of recognition and respect for the right of freedom of others in fulfilling justice in accordance with moral considerations, religious values, security and public order. The death penalty in Indonesia is only applied to very serious crimes in accordance with applicable law. The Constitution in addition to protecting human rights also allows such human rights to be restricted. Keywords: Philosophy of law, death penalty, human rights.